If it's not what You are looking for type in the equation solver your own equation and let us solve it.
1=y/2+7
We move all terms to the left:
1-(y/2+7)=0
We get rid of parentheses
-y/2-7+1=0
We multiply all the terms by the denominator
-y-7*2+1*2=0
We add all the numbers together, and all the variables
-1y-12=0
We move all terms containing y to the left, all other terms to the right
-y=12
y=12/-1
y=-12
| 2/3y+1=16y+8 | | 4x+15=5x+23 | | x+90+53.6=180 | | 58-7x6=0 | | 5h+2=39 | | 0.5x-12+48=90 | | 3x+9=36+6x | | F(3)=7x+5 | | 24-(p+9)=3 | | 89h+45=99h+24 | | -2a+(6+5a)=-3a | | -25=5/2(8r-6)+2r=32 | | 8x-5=6x=29 | | 80-8.49x=46.04 | | 7(y-7)=2(13+1 | | z/30=24 | | -100-50=2x=5x | | 20-13=15x-3x | | V(x)=x(8-2x)(10-2x) | | 10x-5x=90 | | (X+6)(2x+1)=6 | | 13y+17y=99 | | 12-4y=60 | | 2x-4x=100-12x | | 4/3x+2=9x-1 | | 5x-2(3x+1)=180 | | 2n+8n=3n+7 | | 7t-4t=+3-1=29 | | 4t-4t=+3-1=29 | | 4/7=n/24 | | 3.1+3.5(4x-2)=10.1 | | 3.1+3.5*4x-2)=10/1 |